Microtremors HVSR Correlation with Sub Surface Geology and Ground Shear Strain at Palu City, Central Sulawesi Province, Indonesia - Thein, PyiSoe (IJISM, 2014)
In the present study, we have performed microtremor measurements at Palu City, Indonesia for HVSR correlation, which will be used in seismic hazard mapping. We found the correlation between subsurface geology and microtremors HVSR, even in complex geological setting.